The role of placental hormones and metabolites in modulating uterine circulation in physiological and pathological pregnancies - Esposito, Milena; Paulesu, Luana; Mandalà, Maurizio (Frontiers in Endocrinology, 2025)
The adaptation of the uterine circulation during pregnancy is fundamental to ensure an adequate supply of oxygen and nutrients to the fetus, and this process is largely orchestrated by placental hormones/metabolites. In this review, we comprehensively examine the role of placental hormones, growth factors, and proteins in mediating vascular remodeling, vasodilation, and angiogenesis within the uterine circulation under both physiological and pathological conditions. Key molecules such as estrogens, progesterone, relaxin, VEGF, PlGF, and PTHrP, among others, promote structural and functional adaptations of uterine arteries, reduce vascular resistance, and enhance uteroplacental blood flow. Additionally, we discuss the impact of placental dysfunction on the development of pregnancy-related disorders such as preeclampsia, intrauterine growth restriction, gestational diabetes mellitus, and placenta accreta spectrum conditions that share common features of impaired uterine vascular remodeling and altered placental secretome. Furthermore, we explore innovative therapeutic strategies that aim to restore placental and vascular function, including gene therapy, mesenchymal stem cell-based approaches, and targeted nanomedicine. Finally, we highlight the emerging role of placental biomarkers for early diagnosis and risk stratification of vascular complications in pregnancy. Understanding the intricate interplay between placental secretions and the maternal vasculature is critical to advancing the prevention, diagnosis, and treatment of pregnancy complications, ultimately improving maternal and fetal health outcomes.